Translating brand reputation into equity from the stakeholder’s theory: an approach to value creation based on consumer’s perception & interactions - Olukorede Adewole (International Journal of Corporate Social Responsibility, 2024)
Abstract This study is to examine the translation of a reputable brand into equity and how consumers’ perceptions can trigger value creation from commitment and pursuit of CSR by an organization and adopting the same as a brand, lifestyle, and culture, while pointing attention to the stakeholder’s theory as well as pointing to brand interactions from consumer perceptions based on a mixed methods research approach from quantitative and qualitative analyses as presented with a sampling survey of 205 observations and respondents from Roma and neighbourhood. A CSR-based business model tied to the cultural and lifestyles of the people in brand context, while deciphering and delineating consumer behavior, even pointing significantly to the “black box models and rational choices,” would foster effectiveness and efficiency in the operational modules as well as impact on financial performance as unveiled from the qualitative data analysis and inferential statistics, thus emphasizing the significance of brand from the consumer side. It can be inferred that culture and traditional behavior play significant roles in brand perception considering the complexes, unpredictable trends, or patterns associated with consumers’ expressions and behavior in the context of a black box, rational and complex mixes, even justified by the result of the hypothesis testing of the composite attributes and evident from the ‘inference statistics and results, which gave a p–value exceeding 0.05. Conclusively, a CSR–based business model and structure can enhance change transitions from short– term to long– term goals, drive to sustainability, localized stabilization, and sustainable domains. Even brand interactions can be significantly enhanced by CSR, as ascertained by the relatively high R– squared value of 0.8826 and the justification of statistical significance from the factors as indicated by the ‘SEM results and analyses. Organizations can essentially adopt and apply the concept of bran translating to equity from CSR and consumer perceptions when embedded in their business model as a strategic tool in enhancing their performances and finances.